HOW THE NEGATIVE AFFECTIVE RELATION BETWEEN THE SCHOOL COMMUNITY HARMS THE LEARNING OF STUDENTS AT THE STATE SCHOOL PROFESSOR DONIZETTI APARECIDO LEITE - Rocumback Flose, Keila; Conceição Bernucio Lourenço Pereira, Patrícia; Monteiro Júnior, Walfrido (Revista Gênero e Interdisciplinaridade, 2023)
This article addresses the topic: Affectivity and Learning and has as an investigation problem: how can negative affectivity affect student learning? The following research questions are: how does the affective relationship influence learning? How does the negative affectivity with the school community occur? What are the main problems of this school community in relation to affectivity? As a central assumption: negative affectivity impairs students’ learning. The research objectives are: to analyze whether the relationships between the school community are affective. To verify how the negative affective relationship between the school community influences the low levels of student learning. The qualitative and quantitative research was selected in the execution of this research and the case study as an investigation method with the application of a poll with the participation of professors, employees and students.